ENTRE ANGLO-SAXÕES E ESCANDINAVOS: HISTÓRIA E MEMÓRIA EM SAXON STORIES, DE BERNARD CORNWELL Guarapuava 2019 - Soares, Isabelle Maria (2019)
The reading of the literary series Saxon Stories (2004-), by the British author Bernard Cornwell, encourages reflections on the relationship between Scandinavians and Anglo-Saxons in the British territory in the 9th century, which provides an overview of this historical moment. Only the first three volumes of the series will be used as an object of study for this research. Fiction and history come together in order to represent significant moments of the period. Therefore, the goal is to identify manifestations of memory regarding the history of England, by means of the concepts appropriated by Pierre Nora (1993), Maurice Halbwachs (2015), Michael Pollak (1989; 1992) Jacques Le Goff (2013) and Joël Candau (2011). Firstly, we will discuss the memories that flow from the literary work related to its context of production in contemporary times which surround the author and imply questions concerning the studies of gender exteriorized and internalized by the texts being studied. We are also interested in contextualizing the historical time and space of the narrative, the British territory in the 9th century, mainly based on Peter Blair (1966) and Isabela Albuquerque ( 2017), for the Anglo-Saxons; the Brazilian historian Johnni Langer (2007, 2012, 2015, 2017), regarding the Scandinavians; and again the Brazilian researcher Albuquerque (2017), who produced a doctoral thesis which discusses the identity relations between these two peoples in the British territory. Considering the relationship between History and Literature, we will also approach the work as a historical fiction based on the theoretical assumption in Weinhardt (2011) and Bastos (2007), focusing on the confrontation between the Historical Novel as grounded in György Lukács (2011) and the Historiographic Metafiction proposed by Linda Hutcheon (1991). From these points, we support the analysis of the work, in order to identify memories that emerge and reflect historiography and literary fiction.